Dansk national identitet afspejledet i medierne ved OL-fodboldturneringerne 1908-1960 - Jørgensen, Per (Forum for Idræt, 2007)
Per Jørgensen: Danish national identity and the media at the Olympic Games 1908-1960 It has often been said that sport, and not least soccer, plays an important role in the construction of national identity. This is also the case in Denmark. This paper examines how the subject of Danish national consciousness, national feelings and nationalism, in the article collectively called »Danishness«, was culturally expressed through sport journalism in the period 1908-1960. The subject matter is the soccer- tournaments in those specific Olympic Games where Denmark took part. The discourse of the sport journalism in the paper »Politiken« has been hermeneutically analyzed. Research on how nationalism is expressed in one country requires international comparisons to allow theoretical generalizations. Therefore a minor study of the sport journalism of the Swedish newspaper »Dagens Nyheter« has been carried out regarding selected soccer-matches with Swedish participation in the Olympic Games in 1912, 1948 and 1952. Many of the characteristics of present day society referred to as »Danishness« are also explicit in the period 1908-1960 in the newspaper »Politiken«. A comparison between »Politiken« and »Dagens Nyheter« seems to show that the Danish discourse has distinctively Danish characteristics.